2020
DOI: 10.1111/ppl.13294
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of tomato RING E3 ubiquitin ligase gene SlRING1 confers cadmium tolerance by attenuating cadmium accumulation and oxidative stress

Abstract: Heavy metal pollution not only decreases crop yield and quality, but also affects human health via the food chain. Ubiquitination‐dependent protein degradation is involved in plant growth, development, and environmental interaction, but the functions of ubiquitin‐ligase (E3) genes are largely unknown in tomato (Solanum lycopersicum L.). Here, we functionally characterized a RING E3 ligase gene, SlRING1, which positively regulates cadmium (Cd) tolerance in tomato plants. An in vitro ubiquitination experiment sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…In tomato the REALLY INTERESTING NEW GENE 1 (SlRING1) protein is also critical for Cd 2+ tolerance [ 157 ]. Tomato transgenic lines that overexpress SlRING1 displayed higher photosynthetic rates and higher chlorophyll levels, compared to wildtype, when treated with Cd 2+ [ 157 ]. The transgenic lines also showed a reduction in ROS level and overall membrane damage [ 157 ].…”
Section: Heavy Metal Stressmentioning
confidence: 99%
“…In tomato the REALLY INTERESTING NEW GENE 1 (SlRING1) protein is also critical for Cd 2+ tolerance [ 157 ]. Tomato transgenic lines that overexpress SlRING1 displayed higher photosynthetic rates and higher chlorophyll levels, compared to wildtype, when treated with Cd 2+ [ 157 ]. The transgenic lines also showed a reduction in ROS level and overall membrane damage [ 157 ].…”
Section: Heavy Metal Stressmentioning
confidence: 99%
“…Thus, enhanced tolerance to Cd due to induced SlRING1-overexpression is attributed to reduced Cd accumulation and the alleviation of oxidative stress. These findings suggest that SlRING1 is a positive regulator of Cd tolerance, which could be a potential breeding target for improving HM tolerance in plants [ 93 ].…”
Section: New Strategies For Phytoextractionmentioning
confidence: 99%
“…Other studies showed that hormones KT and SA could enhance the Cd tolerance of plants by regulating the metabolism of ascorbate and glutathione, which further maintained redox balance in plant cells (Yan et al 2016, Bashri et al 2021. Ahammed et al (2021) found that tomato RING E3 ubiquitin ligase gene SlRING1 played an important role in fighting against Cd toxicity by regulating the metabolism of ascorbate and glutathione. However, under Cd stress, whether Pr can regulate the metabolism of ascorbate and glutathione through the above hormones and RING E3 ubiquitin ligase gene SlRING1 is still unclear.…”
Section: Original Papermentioning
confidence: 99%